Visual decision aids to support communication and shared decision-making: How are they valued and used in practice? - Janneke Noordman; Désanne Noordam; Jorien van Treeck; Karen Prantl; Patricia Pennings; Petra Borsje; Maud Heinen; Yvette Emond; Ester Rake; Gudule Boland; Sandra van Dulmen (PLoS ONE)
Background It is unknown how visual decision aids support communication and shared decision-making in everyday clinical practice, and how they are perceived by patients with varying levels of health literacy and their healthcare providers. Recently, three visual decision aids have been developed for renal replacement treatment, osteoarthritis of the knee, and osteoarthritis of the hip. This study aims to explore how patients and healthcare providers use and value these visual decision aids. Methods The evaluation of the visual decision aids was performed by coding video-recorded outpatient consultations (n = 35), by conducting reflective practice interviews with healthcare providers (n = 9), and through interviews with patients (n = 29). Consultations were coded using the 5-item OPTION instrument to measure shared decision-making, and self-developed items based on the visual decision aids and user guide. Results Both healthcare providers and patients valued the use of the visual decision aids, especially the overview page with all treatment options. Accordingly, it was observed that most providers mainly used the overview page. However, providers in nephrology discussed the individual treatment pages more often than providers in osteoarthritis care. This study also showed that most providers were unfamiliar with the user guide for the visual decision aids. Conclusion Visual decision aids for nephrology and osteoarthritis care seem particularly useful for patients with limited health literacy. Healthcare providers in this study mainly used the overview page of the visual decision aids. Although this is valued by both providers and patients, it is also important to discuss the individual treatment pages, including the pros and cons, with patients. This study also points to differences between outpatient clinics or departments in the use and implementation of the visual decision aids. The visual decision aids for osteoarthritis are used to a limited extent. In nephrology clinics, the visual decision aid is implemented.